Characterizing Subjective Noisiness in Hospital Lobbies - Chiung Yao CHEN (Archives of Acoustics, 2015)
The present study was conducted in the lobbies of 16 Taiwanese urban hospitals to establish what contributes to the degree of noisiness experienced by patients and those accompanying them. Noise level measurements were then conducted by 15 min equivalent sound pressure levels (LAeq, 15m, dB) during daytime hours. The average LAeq itself was found to be poorly related to perceived noisiness. Levels variations were better correlated, more continual noise may actually be perceived as noisier. According to the findings of a multiple linear stepwise regression model (r = 0.91, R2 = 0.83), the 3 independent variables shown to have the largest effects on perceived noisiness were 1) $1/(L_5−L_{95})$, 2) effective duration of the normalized autocorrelation function $(τ_e, h)$, of all LAeq, 15m over 9–17, and 3) percentile loudness, N5, 15m. These results resemble previous studies that had assumed that a larger fluctuation of noise level corresponds to less annoyance experienced for mixed traffic noise studied in a laboratory situation. As an advanced approach, for hospital noise that consisted of 12 audible noise events, subjective noisiness were evaluated by the noise time structure analyzed by autocorrelation with loudness and levels variation.